KONFIGURASI SISTEM KEMUDI DAN PENGGERAK KENDARAAN TRAKTOR PERTANIAN DALAM BERBAGAI ARAH GERAK - Soemardji, Leo; Mustofa, Mustofa (Jurnal MEKANIKAL, 2012)
This study aims to describe and show the configuration of the integration between the steering system on both front wheel drive system and the controller at the rear wheels on the vehicle type agricultural tractors. The system comprises four tractor steering wheel. Model analysis of the movement of the system displayed good mathematical equation model moves toward forward, rewind and play with various configurations. Further analysis was performed in Mathlab program that makes it easy to see variations of the steering angle, wheel speed drive and motion of different models using the specific parameters that correspond to the size of one type of agricultural tractors. The ability to move the steering wheel in different directions and the steering wheel angle greatly affect the ability of the tractor to resist external forces that occur when the through road, especially elevation and slippery. This analytical model can be developed for other types of agricultural vehicles, such as lawn mowers and off-road vehicles.